Strategic Management of ISDIK Kie Raha in Enhancing Higher Education Competitiveness in North Maluku - Rosita Jainudin (Universitas Muhammadiyah Pontianak, 2026)
Higher education institutions in peripheral regions face challenges in sustaining competitiveness amid increasing educational competition and resource constraints. This study examines strategic management implementation at ISDIK Kie Raha, North Maluku, to enhance institutional competitiveness. Using a qualitative case study, data were collected through interviews, observations, and document analysis involving institutional leaders, lecturers, and administrative staff. The findings reveal that strategic formulation, implementation, and evaluation are conducted but remain insufficiently integrated due to limited analytical capacity, resource constraints, and weak feedback mechanisms. The study implies the need for evidence-based planning, stronger strategic alignment, and performance-based evaluation to support sustainable institutional competitiveness.